(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
So far, no significant modeling of reed biomass availability or assessment of the sustainability of reed products based on life cycle analysis has been conducted in Latvia. Nevertheless, these aspects are crucial for the development of reed-based products, as they help evaluate their market potential and overall socio-economic and environmental impact. This work aims to establish a methodology for modeling the extent of available reed distribution to forecast its future availability, as the availability of reed biomass is a vital prerequisite for utilizing this resource in the national economy. The novelty of this research lies in predicting reed areas based on existing historical data. The modeling is performed using GIS and satellite data.